Two Year Clinical Outcomes of the Subchondroplasty® Procedure for Treatment of Symptomatic Bone Marrow Lesions of the Knee. Issue 7 (29th July 2019) - Hajnik, Christopher; Akhavan, Sam; Wyland, Douglas J.; Cohen, Steven B.; Jazrawi, Laith M.; Youm, Thomas; Loren, Gregory J.; Farr, Jack; Rahme, Marianne Dornbush; Rahme, Marianne; Reischling, Patrick
Objectives: Bone Marrow Lesions (BML) are a common finding on knee MRI. In the knee, BML have a strong correlation to patient-reported pain, function, joint deterioration and rapid progression to TKR. Histologic analyses of BML have demonstrated findings consistent with fracture and bony remodeling of the trabeculae. The Subchondroplasty (SCP®) Procedure aims to treat the bone defects present in the BML by percutaneously filling them with a bone substitute material, designed to flow through intact bone, harden at body temperature and then heal through natural bone turnover. Previous retrospective, single-center case series have demonstrated improvements in patient-reported outcomes. The purpose of this prospective, multi-center study is to evaluate the 2-year clinical and radiographic outcomes of patients with BML of the knee treated with the Subchondroplasty Procedure. Methods: Seventy patients were treated between 2012 and 2017 for BML of the tibial plateau and/or femoral condyle. Self-drilling cannulas were inserted into the BML using arthroscopic and fluoroscopic guidance, then injected with AccuFill® Bone Substitute Material. All patients also underwent arthroscopy to aid in targeting the underlying bony lesion and address intra-articular pathology. MRIs and radiographs were obtained pre-operatively, at 6, 12 and 24 months, with additional radiographs collected at 6 weeks and 3 months. Patient-reported outcomes, including VAS pain, IKDC and KOOS were collected pre-operatively, 2 and 6 weeks, and 3, 6, 12 and 24 months post-operatively. Results: Seventy patients (36 males and 34 females), average age 57 were consented and enrolled in the study. Preoperative K-L grade included 1.4% Grade 0, 2.9% Grade 1, 27.1% Grade 2, 55.7% Grade 3 and 7.1% Grade 4. Fifty eight tibial plateaus and 41 femoral condyles were treated (29 bipolar lesions treated). VAS Pain scores improved from a mean of 6.2/10 pre-op to 2.9/10 at 1 year. IKDC scores improved from mean 33.9 pre-op to 61.3 at 1 year. KOOS scores improved from baseline to 1 year (Fig. 1) with mean KOOS Pain from 45.8 to 73.9, ADL 52.9 to 79.2, Symptoms 49.7 to 71.9, Sports 21.2 to 49.9 and Quality of Life 18.1 to 52.3. All patient-reported outcomes showed statistically significant improvement at one year. Two year outcomes collected to date appear to follow the same trend. The last study subject is due to return in January 2019 at which point the final 2 year analysis will be completed. Six patients (8.6%) converted to arthroplasty (1 UKA and 5 TKA) at one year. To date, the 24 month conversion rate is 16.1% out of 62 subjects. The final conversion rate for 24 months will be calculated after the final subject returns. Radiographs and MRIs demonstrated good incorporation of the AccuFill material through 12 months with evidence of early remodeling and a lack of OA progression in the majority of subjects. Twenty-four month MRIs demonstrate continued remodeling of the AccuFill material. Conclusion: This study presents statistically and clinically-meaningful evidence of improvements in clinical outcomes following Subchondroplasty procedure for BML of the knee. The low conversion rate suggests this less-invasive procedure may delay the need for knee arthroplasty. MR imaging demonstrates good incorporation of the BSM and evidence of remodeling and reduction in material volume over time. Figure 1. KOOS Pain Scores Table 1. KOOS Pain Scores KOOS Pain Subscale Score Interval N Mean SD Min Max 95% CI Pre-op 69 45.8 14.1 8.3 77.8 (42.4, 49.2) 2 weeks 67 50.9 19.6 0.0 91.7 (46.1, 55.7) 6 weeks 68 65.7 17.4 25.0 100.0 (61.5, 69.9) 3 months 62 73.1 19.1 16.7 100.0 (68.2, 77.9) 6 months 62 70.3 21.1 8.3 100.0 (65.0, 75.7) 1 year 56 73.9 20.6 13.9 100.0 (68.4, 79.4)